Efficient E-Government Services, Constraints and Problems of Technical Applications and Software and the Transition to Smart Government - Seleman, Yasser A (Arab Journal for Sciences and Research Publishing, 2016)
The e-governance is the concept and structure of the system and the functions and activities of all activities and processes in e-business on the one hand the level of e-government and business on the other.              Because the government sector as a significant proportion of the total economic sectors in most countries of the world, and the fact that dealing with the public sector is not limited to the class and not others, but prevail all citizens and residents, institutions and others, and the fact that this multi-dealing in quality, methods and how it is done and models for different procedures and steps implemented and locations between the corridors of government departments, the concept of e-government came as an ideal way for the government to enable them to take care of the interests of the public from individuals and institutions electronically using cutting-edge technology without the need for the applicant to move between government departments.
Keywords: E-Government; Constraints Technical Applications; Smart Government; Services